Implosion : can America recover from its economic and spiritual challenges in time? - Rosenberg, Joel C. 1967- (Carol Stream, Ill. : Tyndale House Publishers, 2012)
Bestselling author and international political expert Joel C. Rosenberg tackles the question: Is America an empire in decline or a nation poised for a historic Renaissance? America teeters on a precipice. In the midst of financial turmoil, political uncertainty, declining morality, the constant threat of natural disasters, and myriad other daunting challenges, many wonder what the future holds for this once-great nation. Will history's greatest democracy stage a miraculous comeback, returning to the forefront of the world's economic and spiritual stage? Can America's religious past be repeated today with a third Great Awakening? Or will the rise of China, Russia, and other nations, coupled with the US's internal struggles, send her into a decline from which there can be no return? Implosion helps readers understand the economic, social, and spiritual challenges facing the United States in the 21st century, through the lens of biblical prophecy. - Publisher.
Includes bibliographical references and index.
Keywords: Forecasting -- Religious aspects -- Christianity; End of the world; Prophecy -- Christianity; United States -- Forecasting; United States -- Social conditions -- 21st century; United States -- Economic conditions -- 2009-